Switching intention to Grammarly premium among postgraduate students in Malaysia - Ang, Ying Ying; Ang, Xuan Wei (2024)
As postgraduate students in Malaysia want more sophisticated features to improve their academic writing, they are increasingly shifting from free to premium services in digital tools like Grammarly. The "switching intention" of these students is examined in this study, with an emphasis on the variables influencing their choice to upgrade to Grammarly Premium. Even though the free version is widely available, many students still give the premium version serious thought because of its improved features, which include sophisticated grammar and plagiarism checks, tone adjustments, and word suggestions—all of which are essential for writing academic work of the highest calibre. This study investigates the psychological, economic, and practical factors that lead postgraduate students in Malaysia to switch using Keaveney's model of switching intention. The study explores the intricacies of the difficulties Malaysian students encounter in achieving language competency, the function of English as a medium of instruction in postsecondary education, and the perceived usefulness of Grammarly Premium's features in assisting students in meeting these difficulties. The goal of the research is to offer a thorough knowledge of the variables influencing students' intention to switch by combining quantitative and qualitative methodologies. It is anticipated that the study's conclusions will have a big impact on software developers, educational institutions, and students themselves. Teachers may better assist students in their academic journeys by knowing the factors that led them to upgrade to Grammarly Premium, and software suppliers can customise their products to fit the unique requirements of the academic community. In the end, this study adds to the larger conversation about digital tools in education by illuminating the ways in which technology might be used to improve academic performance in a multicultural and multilingual setting such as Malaysia. Switching Intention to Grammarly Premium among Postgraduate Students in Malaysia xv Keywords: Grammarly Premium, Switching Intention, Postgraduate Students, Keaveney Theory, Consumer Behavior, Service Quality, Digital Writing Tools, Technology Adoption, Educational Technology, Malaysia